Epidemiology of Tympanoplasty in Children following Tympanostomy Tube Placement. (2nd September 2014) - Alrwisan, Adel; Antonelli, Patrick J.; Winterstein, Almut G.
Abstract : Objectives: Quantify the incidence rate of tympanoplasty after tympanostomy tube (TT) insertion in children. Methods: This was a retrospective cohort study of healthy children <18 years old using Medicaid Extract Files from 1999 to 2004. All subjects received TTs and had at least 6 months continuous Medicaid eligibility prior to TTs. We followed patients for 2 years after TTs. The Kaplan‐Meier procedure was used to estimate time to tympanoplasty. Results: There were 270, 408 children with billing records for TTs, and 141, 243 met inclusion criteria with a follow‐up time of 217, 431 patient‐years. Median age at TTs was 1.62 year, with 58.5% placed at <2 years. Subsequent tympanoplasty was performed in 963 (0.68%), with 324 at age 2‐4 years. The median age at tympanoplasty was 5.1 years. Median time from TTs to tympanoplasty was 450 days. The incidence rate of tympanoplasty was 44 cases per 10, 000 patient‐years (95% confidence interval 41 to 47). Conclusions: Tympanoplasty following TTs is not uncommon. These repairs are commonly performed in preschool children and often within 2 years of TT placement.